The Philosophical Construction of Legal Justice by John Rawls and Gustav Radbruch and Its Relevance in the Context of the Indonesian Legal System - Tohari, Ilham; Musoffa, Ahmad; Rosidah, Aminatur; Toriqirrama, Faby (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
The purpose of this article is to explore the philosophical constructions of legal justice proposed by two prominent thinkers, John Rawls and Gustav Radbruch, and assess their relevance in the context of the Indonesian legal system. Employing a qualitative approach, an in-depth analysis is conducted on their original works, including Rawls'